نظم ادارة الجودة في المحاكم بسلطنة عمان: دراسة حالة - Salim Mohammed Omar Ojaili
The courts are considered the most important modern Institutions which deal with different disputes and problems and refute any defect that is scouring society. This study aims to identify some possible solutions to these remarkable organizations since they suffer from many problems and obstacles that hinder the performance of employees and the dealers. However, it is an urgent issue to suggest solutions that develop these entities and pay more attention for them to promote them to higher levels of development. The study was followed to achieve this analytical descriptive approach, through which the scientific methods of quality management in court management were explained, and the available information was collected using the methods of quantitative analysis theory. The researcher relied on using survey results with (220) questionnaires to measure their application to a sample of the staff of the departments and departments of the courts Oman, a total of (201) solutions for analysis, The study used the SPSS program as a tool to analyze the data. The study found that quality management is based on a set of important foundations must be available in the courts in order to be carried out by the quality management, and the application of the principles and concepts of quality management helps the courts to better use and optimize their material and human resources, and work not to waste through the elimination of obstacles The quality management philosophy is defined as an innovative approach to the management of organizations such as court management, which aims to achieve organizational goals and increase the efficiency of its employees through the continuous improvement of the quality system. There are urgent social and technical systems and administrative systems, and there is an urgent need to apply quality methods in the Omani courts.Although the service in the courts is difficult to apply quality methods, as it is not a quantitative goal as it is a socio-human civilized goal, but it is not impossible, as confirmed by Many experts in other areas of quality, and the management of the courts to take into account the attribution of qualified individuals scientifically and practically, as a prerequisite for the application of quality management method, and to pay attention to innovative ideas and develop the skills of workers, especially in the areas of quality, so that the quality of attention The use of quality management techniques can reduce the cost to the courts of administering the courts.The courts and their administrations should be aware that the costs of implementing quality systems and administrations, while high at the outset, will be an economic and incentive hub for survival.